المنهجُ الدَّعويّ والتَّربويّ في تصنيف الحديث النَّبويّ: وقفاتٌ حديثيَّة مع الإمام عبد السَّلام ياسين - Abdul Rahman Hussein Obeid; Mohd Zohdi Mohd Amin; Nur Saadah Hamisan @Khair; Norzulaili Mohd Ghazali; Nusairah Ramli; Robiatul Adawiyah Mohd @ Amat (Universiti Sains Islam Malaysia, 2026)
Indexed by MyCite